Experimental investigation of main controls to methane adsorption in clay-rich rocks - Ji, Liming; Zhang, Tongwei; Milliken, Kitty L.; Qu, Junli; Zhang, Xiaolong (Applied geochemistry, 2012)
► The difference in clay mineral type is one key element controlling CH4 adsorption in clay-rich rocks. ► BET surface area is a primary proxy for CH4 adsorption capacity in clay-rich rocks. ► Clay type affects gas-sorption capacity and the presence of moisture can greatly reduce gas-sorption capacity. ► Quantitative model prediction is developed to estimate the methane sorption capacity of organic-lean shales. In this study a series of CH4 adsorption experiments on clay-rich rocks were conducted at 35°C, 50°C and 65°C and at CH4 pressure up to 15MPa under dry conditions. The clay-dominated rock samples used are fresh samples from quarries and mines. Samples are individually dominated by montmorillonite, kaolinite, illite, chlorite, and interstratified illite/smectite. The experimental results show that clay mineral type greatly affects CH4 sorption capacity under the experimental conditions. In terms of relative CH4 sorption capacity: montmorillonite≫illite/smectite mixed layer>kaolinite>chlorite>illite. Physisorption is the dominant process for CH4 absorption on clay minerals, as a result, there is a linear correlation between CH4 sorption capacity and BET surface area in these clay-mineral dominated rocks. The abundance of micro-mesopores in the size range of a few to a few 10s of nanometers in montmorillonite clay and illite–smectite interstratified clay results in large BET surface area values for these mineral species. A good linear relationship between the natural logarithm of Langmuir constant and the reciprocal of temperature exists for clay-mineral dominated rocks, which provides a way to quantify the impact of clay mineral type on gas adsorption capacity. Thermodynamic parameters, the heat of CH4 adsorption and the standard entropy, are calculated based on this linear correlations. The heat of adsorption (q) and the standard entropy (Δso) range from 9.4 to 16.6kJ/mol and from −64.8 to −79.5J/mol/K, respectively, values considerably smaller than those for CH4 adsorption on kerogens. Thus, it is expected that CH4 molecules may preferentially occupy surface sites on organic matter, in addition, the clay minerals are easily blocked by water. As a consequence, organic-rich mudrocks possess a larger CH4 sorption capacity than clay-dominated rocks lacking organic matter.